Prevalence and outcome of hyponatremia in patients admitted with COVID-19 - Shetty, Vishranth N.; B., Jayaprakash; Rao, Gurukanth (International Journal of Advances in Medicine, 2022)
Background: Hyponatremia occurs in up to 30% of patients with pneumonia and is associated with increased morbidity and mortality. The prevalence of hyponatremia associated with coronavirus disease 2019 and the impact on outcome is unknown. We aimed to identify the prevalence, and outcome of patients having hyponatremia admitted with COVID-19. Methods: This was a retrospective observational study conducted among admitted adult patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in Srinivas institute of medical sciences and research centre, Mukka, Surathkal. Results: This difference in hyponatremia was statistically significant with regard to age (p<0.001), respiratory rate (p=0.002), SpO2 (p=0.029), total counts (p=0.03), CRP (p=0.005), and d-dimer (p=0.015). Conclusions: In patients with COVID-19, age, hypotension, respiratory rate, SpO2, total counts, CRP, and D-Dimer have significant correlation with hyponatremia. Also, patients with COVID-19 and hyponatremia have higher rates of mechanical ventilation and mortality.